Parcours migratoires féminins à Parme (Italie du nord) selon différentes sources d’information : Étude de cas - Vincenza Pellegrino; Enzo Lucchetti; Gilles Boëtsch (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
The present study concerns contemporary migration experiences characterized by different factors, such as the country of origin and the gender of migrants. The migration paths linking the city of Parma (northern Italy) with the various countries of origin have been analysed on the basis of information taken from the Population Register of the Town Council of Parma (1989-2000), as well as information obtained in the course of a survey (1999-2002) conducted by the Migrants Health Center of the Local Health Authorities. Thus our project has a methodological orientation: it underlines the utility of integrating different sources and survey methodologies when undertaking a study of migrations. We have explored in depth the most numerous women’s migration paths in our area of study (those of Tunisian, Filipina, Nigerian, Moldavian and Ukrainian women) and we have highlighted the particular features of these migration circuits, according to age, marital status, family relationships and the mother-daughter separation induced by the migration. Finally, the Cluster Analysis method has enabled us to “measure” the distance between the different migration profiles and we have underlined the high degree of variability existing within the phenomenon of immigration.